Positive Personality Model: its relation to optimal functioning in active workers - de la Iglesia, Guadalupe (2019)
This research aimed to analyzewhether positive traits could explain optimal functioning, the combination of high well-being and performance, of active workers. The sample comprised 400 active Argentinean workers between the ages of 18 and 66 years old (MAGE=36.50, SD=11.81, 49.5% male, 50.5% female). Multiple lineal regressions revealed that positive traits increase the explained variance of the work variables (performance, satisfaction and well-being) in comparison to a prediction model that only included normal traits. Also, discriminant analysis revealed that of all traits, positive and normal, the only one that better discriminated the high/low optimal functioning groups was the positive trait sprightliness.